2017
DOI: 10.5194/acp-17-12361-2017
|View full text |Cite
|
Sign up to set email alerts
|

Fast heterogeneous N<sub>2</sub>O<sub>5</sub> uptake and ClNO<sub>2</sub> production in power plant and industrial plumes observed in the nocturnal residual layer over the North China Plain

Abstract: Abstract. Dinitrogen pentoxide (N 2 O 5 ) and nitryl chloride (ClNO 2 ) are key species in nocturnal tropospheric chemistry and have significant effects on particulate nitrate formation and the following day's photochemistry through chlorine radical production and NO x recycling upon photolysis of ClNO 2 . To better understand the roles of N 2 O 5 and ClNO 2 in the high-aerosol-loading environment of northern China, an intensive field study was carried out at a high-altitude site (Mt. Tai, 1465 m a.s.l.) in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
99
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 77 publications
(131 reference statements)
15
99
0
1
Order By: Relevance
“…A previous methods comparison of data from winter 2011 in Colorado also showed similarity between Methods 2 and 3, with an average ϕ (ClNO 2 ) value of 0.05 ± 0.15 using Method 2 (Riedel et al, ) and a mode of ~0.06 derived from a box model similar to the one used here (Wagner et al, ). An additional comparison of Method 2 and the right‐hand side of (calculated from the steady state approach and observed ClNO 2 production rates) by Z. Wang, Wang, Tham, et al () found absolute agreement within 0.03 for the campaign average ϕ (ClNO 2 ) value at a ground site in northern China during summer 2017.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…A previous methods comparison of data from winter 2011 in Colorado also showed similarity between Methods 2 and 3, with an average ϕ (ClNO 2 ) value of 0.05 ± 0.15 using Method 2 (Riedel et al, ) and a mode of ~0.06 derived from a box model similar to the one used here (Wagner et al, ). An additional comparison of Method 2 and the right‐hand side of (calculated from the steady state approach and observed ClNO 2 production rates) by Z. Wang, Wang, Tham, et al () found absolute agreement within 0.03 for the campaign average ϕ (ClNO 2 ) value at a ground site in northern China during summer 2017.…”
Section: Resultsmentioning
confidence: 98%
“…In this section, four methods are applied to WINTER data in an attempt to provide a direct comparison and evaluation of methods commonly used in past literature. Due to the difference in aircraft and ground‐based observational data, ϕ (ClNO 2 ) derivations using steady state‐derived kN2O5 in (used by Tham et al, ; X. Wang, Wang, Xue, et al, ; Z. Wang, Wang, Tham, et al, ) and the ratio of ClNO 2 to p NO 3 − production rates (used by Wang et al, ) could not be compared to box model results. Each additional method tested here is described below and assumes that heterogeneous production is the only source of ClNO 2 , and that ClNO 2 is stable overnight.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous air pollution control in China 10 primarily focused on the reduction of anthropogenic emissions of sulfur dioxide (SO 2 ), given the dominant contributions of sulfate (SO 4 2-) to the PM 2.5 and acid depositions (Hao et al, 2000 and2007). In the last decade, about 75% reduction of SO 2 emissions in China has successfully resulted in decreases in the ambient levels of both SO 2 and aerosol SO 4 2-in fast-developing regions including the NCP Li et al, 2017). In comparison,…”
mentioning
confidence: 99%